Enhanced radiation shielding via incorporating europium oxide in 316L stainless steel: Synthesis, physical, microstructural, shielding, and mechanical properties - Tekin, H. O.; Yayla, Nihal; Albayrak, Muhammet Gokhan; Guler, Omer; Sen Baykal, Duygu; Alkarrani, Hessa; ALMisned, Ghada (Elsevier, 2025)
316L stainless steel is widely utilized in various industries due to its excellent corrosion resistance, mechanical strength, and biocompatibility, making it a preferred material for applications in nuclear filed. However, enhancing its radiation shielding and mechanical properties through reinforcement strategies, such as the addition of high-Z materials like Europium(III) oxide, is crucial for extending its functionality in high-radiation environments, where improved performance is essential for safety and durability. In this study, 316L stainless steel composites reinforced with varying amounts of Eu2O3 (1%, 5%, 10%, and 20%) were synthesized and investigated for their structural, mechanical, and radiation shielding properties. X-ray diffraction (XRD) analysis revealed that the face-centered cubic (FCC) structure of the steel matrix was preserved up to 5% Eu2O3 reinforcement, while higher concentrations led to phase formation and crystallographic changes. Scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) analysis showed uniform element distribution at low reinforcement levels, with particle clustering at 20% Eu2O3. Transmission factors (TFs) were evaluated using PHITS simulations for photon energies of 0.662 MeV, 1.1732 MeV, and 1.3325 MeV. The 20% Eu2O3 composite exhibited the lowest TF and highest attenuation properties, confirmed by mass and linear attenuation coefficients. Elastic modulus values decreased from 224.46 GPa in pure 316L to 189.26 GPa with 20% Eu2O3 reinforcement, reflecting the inverse relationship between mechanical stiffness and radiation shielding performance. Benchmarking against other shielding materials demonstrated superior performance of the Eu2O3-rein- forced steel in gamma-ray attenuation. The 20% Eu2O3 composite shows strong potential for applications in nuclear radiation shielding where attenuation efficiency is prioritized over mechanical properties.
Keywords: 316L stainless-steel; Rare-earth oxide; Europium oxide; Nuclear radiation shielding